2021
DOI: 10.1016/j.heliyon.2021.e08116
|View full text |Cite
|
Sign up to set email alerts
|

Cyto-genotoxic potential of petroleum refinery wastewater mixed with domestic sewage used for irrigation of food crops in the vicinity of an oil refinery

Abstract: Petroleum refinery wastewater combined with domestic sewage were collected from the open channel in the vicinity of Mathura oil refinery, UP (India) and analysed by inductively coupled plasma optical emission spectrometry (ICP-OES) and gas chromatography-mass spectrometry (GC-MS) for elemental analysis and organic pollutants, respectively. Several potentially toxic and non-toxic elements were found to be present in the wastewater samples. GC-MS analysis revealed the presence of several organic contaminants inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…On the other Khatoon & Malik. [87], studied petroleum refinery wastewater that was combined with domestic sewage and reported the pH of the wastewater to be 7.82 similar to S-1, while the EC was 3460 μS/cm, salinity was 2.01 PSU, and TDS and COD as 1910 ± 54.5 and 310 ± 32.1, respectively.…”
Section: Physiochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other Khatoon & Malik. [87], studied petroleum refinery wastewater that was combined with domestic sewage and reported the pH of the wastewater to be 7.82 similar to S-1, while the EC was 3460 μS/cm, salinity was 2.01 PSU, and TDS and COD as 1910 ± 54.5 and 310 ± 32.1, respectively.…”
Section: Physiochemical Analysismentioning
confidence: 99%
“…The finding of this study was in line with Al-Kaabi et al [63] also reported similar results and found that the metals Zn, Cd, Cu, and Ni had the highest concentrations, 4.98 mg/L, 0.050 mg/L, 0.62 mg/L, and 7.080 mg/L, respectively. Khatoon & Malik [87]. and Rasheed & Saleh [90].…”
Section: Heavy Metal Analysis Of the Collected Samplesmentioning
confidence: 99%
“…China has made significant investments in research aimed at enhancing sewage treatment technology and infrastructure [ 33 , 34 ]. On the other hand, India is focusing on the reuse and recovery of water resources as a strategic approach [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of bacteria, the umuC and Ames tests emerged as the most frequently employed methods [ 35 , 58 , 69 , 94 ]. Notably, our observations indicate that the umuC test demonstrated greater efficiency compared to the Ames test.…”
Section: Introductionmentioning
confidence: 99%
“…The existing methods for automatic identification of titration end-point can be divided into three main categories ( Table 1 ), i.e., potential identification [ 13 ], color identification, and artificial intelligence identification. The potential identification method applies indicator electrodes to detect potential changes in solution reactions [ 14 ] and indicates titration end-point with potential abrupt changes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%